2000
DOI: 10.1074/jbc.m002161200
|View full text |Cite
|
Sign up to set email alerts
|

The Gene for a Novel Member of the Whey Acidic Protein Family Encodes Three Four-disulfide Core Domains and Is Asynchronously Expressed during Lactation

Abstract: Secretion of whey acidic protein (WAP) in milk throughout lactation has previously been reported for a limited number of species, including the mouse, rat, rabbit, camel, and pig. We report here the isolation of WAP from the milk of a marsupial, the tammar wallaby (Macropus eugenii). Tammar WAP (tWAP) was isolated by reverse-phase HPLC and migrates in SDS-polyacrylamide gel electrophoresis at 29.9 kDa. tWAP is the major whey protein, but in contrast to eutherians, secretion is asynchronous and occurs only from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
67
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 53 publications
4
67
0
Order By: Relevance
“…For example, it has been suggested that WAP may be a source of cysteine for hair growth of pouch young because WAP contains a large number of cysteine residues [9]. It has been also suggested that WAP may contribute, via milk, to the development of hair in rodents, which are born with minimal fur coverage [7]. On the other hand, Nicholas et al [8] has suggested that WAP may influence the rate of development of the gut of the young via milk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been suggested that WAP may be a source of cysteine for hair growth of pouch young because WAP contains a large number of cysteine residues [9]. It has been also suggested that WAP may contribute, via milk, to the development of hair in rodents, which are born with minimal fur coverage [7]. On the other hand, Nicholas et al [8] has suggested that WAP may influence the rate of development of the gut of the young via milk.…”
Section: Discussionmentioning
confidence: 99%
“…The forced expression of exogenous WAP significantly impaired the proliferation of EpH4 cells, whereas it did not affect that of . Recently, it has also isolated from the milk of pigs [5,6], and three marsupial species, tamer wallaby [7], red kangaroo [8], and brushtail possum [9]. Expression of the WAP gene is regulated by lactogenic hormones, and the level of mo use WAP m RN A in the m am m ary gla nds incr eases t hous ands -fo ld between non-lactation and mid-lactation [10].…”
mentioning
confidence: 99%
“…This four-disulfide core structure was first described in whey acidic protein in mouse milk and thus was named the "WAP motif" (7). Members of the family of WAP motif proteins contain one to three WAP motifs, many of which have proteinase inhibitor activity and/or antibacterial activity (8,9). Trappins are unique in having TGS domains in their N termini among diverse family members of WAP motif-containing proteins that include toxins, pollen allergens, serine proteinase inhibitors, growth inhibitors, calcium transport inhibitors, and others whose functions have not yet been determined (10 -17).…”
mentioning
confidence: 99%
“…hey acidic protein (WAP) has been identified in the milk of a wide range of laboratory animals rodents [1,2], as well as in camels [3], rabbits [4], pigs [5], and three marsupial species, the tammar wallaby [6], brushtail possum [7], the red kangaroo [8]. In mice and rabbits, the expression of the WAP gene occurs in mammary epithelial cells during late pregnancy and throughout lactation, and is regulated by a variety of lactogenic hormones, including insulin, glucocorticoid, and prolactin [9][10][11][12][13][14].…”
mentioning
confidence: 99%